Contaminant spreading by natural convection in a box - Tran, Tran Van; Thang, Nguyen Ngoc; Thuy, Nguyen Thi (Vietnam Journal of Mechanics, 2016)
In this paper the spreading of a contaminant accompanied with natural convection in a box is numerically simulated. The box may be considered as a cooking room or a working place where some sources of heat and contaminant are in the simultaneous action. The box floor is supposed to be divided into several domains with different boundary conditions for temperature or heat flux. Here the purpose of the simulation is to understand the contaminant spreading process in the box under the influence of a convective motion. The model can be also applied for an enclosure with separated parts differentially heated by the sunlight on its boundaries. A good knowledge of this process is very useful for setting an efficient ventilation scheme. In this paper the finite difference method based on the Samarski scheme with ADI technique is applied for numerical simulation. Here the box floor is divided into two domains of equal sizes but with different temperature or heat flux. The contaminant source locates in the middle of the box bottom. The simulation shows that over the part of the floor where temperature or heat flux is greater the contaminant concentration is lager. That result is in the accordance with the experiment done in the framework of this investigation.